The effects of exercise training intensification on glucose disposal in elite cyclists - Manetta, J.; Brun, J. F.; Mercier, J.; Prefaut, C. (International Journal of Sports Medicine, 2000)
To assess the effect of training on glucose disposal, we performed a longitudinal study of 11 elite cyclists before and after 4 months of intensive training compared to 11 sedentary subjects. Insulin sensitivity (SI) and glucose effectiveness (Sg) were measured using Bergman's minimal model. Sg includes basal insulin effectiveness (BIE) and a parameter termed glucose effectiveness at zero insulin (GEZI). After overnight fasting glucose was administered intravenously (0.5 g x kg(-1), 30% solution given over 3 min), and insulin (0.02 U x kg(-1), 1 -2U) was injected immediately after 19 min. Sg, SI and BIE, were significantly higher in elite cyclists both before and after training than in sedentary subjects (P < 0.01). However, the non-insulin-dependent component of Sg (GEZI) was higher only after the intensive training in the cyclists (3.31 +/- 0.67% x min(-1)) than in sedentary subjects (1.7 +/- 0.2% x min(-1), P < 0.02). We conclude that insulin sensitivity (SI) and glucose effectiveness (Sg) are higher in elite cyclists than in sedentary subjects and that these high and almost optimal values are not further improved by additional training. However, the improvement in GEZI, as reflected by the difference between post-training GEZI and sedentary control values, raises the possibility of an increase of the non-insulin-mediated mobilization of glucose transporters.